Neo-Baroque Flowers in Contemporary Architecture - Francesco Del Sole (Athens Journal of Architecture)
Many historians have attempted to define Neo-Baroque in contemporary architecture. Yet, leafing through the manuals, it is not possible to find a definition of this phenomenon, described as “a hypothesis waiting to be developed”. This paper attempts to enter the debate, defining Neo-Baroque not as a mere citation practice, but as a cultural style that identifies today’s society, made of instability and restless expectations. To better understand the contemporary Neo-Baroque soul, the architectural historian must move using those same tools that animate Baroque aesthetics, trying to connect different times and concepts in order to realize relational subtleties that, in Baroque treatises, “are called flowers”. The formal value of Baroque architecture was rehabilitated in the 20th century by architects such as Paolo Portoghesi who, in parallel with the writing of the first manuals on the Baroque, intrinsically reproposed neo-Baroque forms in his projects, making his architecture “blossom” through that dynamic of folds that is well described by the philosophy of Gilles Deleuze. This folding will become a real working method for architects of the caliber of Frank Gehry who stretch and distend forms to replace the lost center with the fragmentation of viewpoints. Through an excursus of the most important “neo-Baroque flowers” of contemporary architecture, the contribution is an invitation to reflect on that aesthetic in which fold upon fold, fold within the fold, the neo-Baroque flowers express the same qualities as the flowers present in 17th-century architecture in plan and ornament: ephemeral, precarious, but also cultured citations and, in the words of Eugene D'Ors, “forms that fly”.